Vocal Process Granulomas: A Systematic Review of Treatment. (May 2014) - Karkos, Petros D.; George, Michael; Van Der Veen, Jan; Atkinson, Helen; Dwivedi, Raghav C.; Kim, Dae; Repanos, Costa
Objectives: Vocal process granulomas (VPGs) are benign laryngeal lesions with controversial treatment and a tendency to recur. There are several treatment options with unpredictable results, high recurrence rates, and disappointing long-term outcome. The aims of this article are to focus on evidence-based current treatment strategies for primary lesions and recurrences. Data Sources: The data came from a systematic review of the literature. Methods: Main outcome measures were recurrence rate, reduction, and/or complete resolution. Inclusion criteria included English literature, randomized and nonrandomized trials, prospective and retrospective studies, and primary and recurrent cases. Exclusion criteria included case reports, teaching reviews, and papers not focusing on treatment. Results: The time frame of the included studies was from 1997 to 2012. There are 6 different treatment options (single or combined) for VPG. Antireflux medication is the mainstay treatment and when combined with lifestyle changes and voice therapy results in the lowest recurrence rate. "Bloodless" in-office or in-theater laser techniques appear to have lower recurrence rates when compared to traditional cold steel microlaryngoscopy techniques, especially for recurrences. Conclusions: There is level 2A evidence that antireflux treatment is the main treatment strategy for vocal process granulomas with surgery reserved only for failures of medical treatment or airway obstruction or when diagnosis is in doubt.